Acute formoterol administration has no ergogenic effect in nonasthmatic athletes - Stewart, I. B.; Labreche, J. M.; McKenzie, D. C. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: To determine the effect of formoterol (formoterol fumarate dihydrate) on the aerobic and anaerobic capacities of highly trained athletes. METHODS: 10 male athletes (age = 26.2 +/- 0.9, VO2max = 65.6 +/- 2.4 mL.kg[minus sign]1.min[minus sign]1) with minimal bronchial reactivity to aerosols (i.e., negative methacholine challenge test) completed three identical exercise sessions differing only by the medication administered. Formoterol (F) a long-acting [beta]2-agonist, presently not approved for international competition by the I.O.C. Medical committee, was compared with salbutamol (S), an accepted bronchodilator, and a placebo (P). Formoterol (12 [mu]g), salbutamol (400 [mu]g), or placebo was administered by a Turbuhaler, 10 min before exercise testing in a double-blind, randomized, three-way crossover design. Testing sessions included a Wingate anaerobic test followed 15 min later by an incremental cycle ergometer test to exhaustion. RESULTS: There were no significant differences between the groups in VO2max (F = 66.5 +/- 2.7; S = 67.8 +/- 2.5; P = 67.5 +/- 2.1 mL.kg[minus sign]1.min[minus sign]1) or Wingate peak power (F = 885 +/- 40; S = 877 +/- 40; P = 885 +/- 44 W) values. During the maximal aerobic test, no differences were observed in maximum minute ventilation, respiratory exchange ratio, heart rate, or work between the three experimental conditions. Also, there were no differences in the Wingate anaerobic test variables, total work, or fatigue index. CONCLUSION: Formoterol, administered in one aerosolized therapeutic dose, does not have an ergogenic effect in elite athletes without asthma.